2020
DOI: 10.3389/fspas.2020.00027
|View full text |Cite
|
Sign up to set email alerts
|

Binary Neutron Star Mergers After GW170817

Abstract: The first combined detection of gravitational waves and electromagnetic signals from a binary neutron star (BNS) merger in August 2017 (an event named GW170817) represents a major landmark in the ongoing investigation of these extraordinary systems. In this short review, we discuss BNS mergers as events of utmost importance for astrophysics and fundamental physics and survey the main discoveries enabled by this first multimessenger observation, including compelling evidence that such mergers produce a copious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Our results suggest that this constraining power will improve when numerical models of merger outflows, telescope sensitivity, and GW detectors progress (see, e.g., Chornock et al 2019;Cowperthwaite et al 2019;Palmese et al 2019). Currently, significant effort is underway to add more sophisticated treatments of microphysical processes to numerical models, as well as increase the coverage of the parameter space studied with these models (Baiotti & Rezzolla 2017;Shibata & Hotokezaka 2019;Ciolfi 2020;Dietrich et al 2021;Ruiz et al 2021). The Vera Rubin Observatory, an optical, wide-field telescope expected to begin operations in 2021 (Ivezić et al 2019), will have a large impact on taking high-accuracy EM data and detecting GW events at larger distances, while telescopes such as ZTF (Dekany et al 2020) and (near-future) dedicated GW follow-up telescopes such as BlackGEM (Bloemen et al 2016) and GOTO (Gompertz et al 2020) will increase the number of detected EM counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that this constraining power will improve when numerical models of merger outflows, telescope sensitivity, and GW detectors progress (see, e.g., Chornock et al 2019;Cowperthwaite et al 2019;Palmese et al 2019). Currently, significant effort is underway to add more sophisticated treatments of microphysical processes to numerical models, as well as increase the coverage of the parameter space studied with these models (Baiotti & Rezzolla 2017;Shibata & Hotokezaka 2019;Ciolfi 2020;Dietrich et al 2021;Ruiz et al 2021). The Vera Rubin Observatory, an optical, wide-field telescope expected to begin operations in 2021 (Ivezić et al 2019), will have a large impact on taking high-accuracy EM data and detecting GW events at larger distances, while telescopes such as ZTF (Dekany et al 2020) and (near-future) dedicated GW follow-up telescopes such as BlackGEM (Bloemen et al 2016) and GOTO (Gompertz et al 2020) will increase the number of detected EM counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of GW170817, the eventual GW signal of the black hole ring-down was too weak to confirm if or when this collapse had occurred (Abbott et al 2017d). This single event represented a breakthrough in the understanding of merger physics and the study of the origin of heavy elements in the Universe (for a review, see Ciolfi 2020). Also, it allowed the first standard siren measurement of the Hubble constant (Abbott et al 2017a;Hotokezaka et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…From the study of PSR B1913+16, it was found that the loss in energy of BNS system and reduction in orbital distance increases the amplitude and luminosity of GWs (Abbott et al, 2017) [5] , and with that the emission of EM waves increases. By combining the GWs luminosity from the BNS system and EM waves redshift of the host galaxy will make it possible to find the Hubble constant from GW standard siren determination (Ciolfi et al, 2020) [26] .…”
Section: Binary Neutron Star (Bns)mentioning
confidence: 99%
“…The color scale showing the amplitude of GWs signal originated from the source GW170817 (Wynn, 2018) [24] . [26] . [27] .…”
Section: Fig 15mentioning
confidence: 99%